2021
DOI: 10.7759/cureus.14689
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Toward Prostate Cancer and Its Screening Methods Among Primary Care Patients in King Abdulaziz Medical City, Riyadh, Saudi Arabia

Abstract: The aim of the study was to evaluate the knowledge, attitude, and practice toward prostate cancer and its screening methods among patients attending primary care facilities in King Abdulaziz Medical City (KAMC) in Riyadh, Saudi Arabia. Materials and methodsA cross-sectional survey was conducted on a random sample of 385 men. The questionnaire was distributed using a non-random sampling method (convenience sampling) that included 13 questions that assess the knowledge, attitude, and practice of adult male patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In reviewing the literature, there was no study measuring the practice of individuals regarding gastric cancer protective behaviors. However, the results of other studies conducted on other types of cancer were indicative of the poor practice of individuals in showing protective behaviors (30)(31)(32)(33), which is not consistent with the results of the present study. This discrepancy might be due to the different sorts of cancers examined in various studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In reviewing the literature, there was no study measuring the practice of individuals regarding gastric cancer protective behaviors. However, the results of other studies conducted on other types of cancer were indicative of the poor practice of individuals in showing protective behaviors (30)(31)(32)(33), which is not consistent with the results of the present study. This discrepancy might be due to the different sorts of cancers examined in various studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the majority of men had adequate knowledge about prostate cancer in terms of whether prostate cancer be diagnosed and treated with 86.7% and have the similar value compared with other studies of 82.1% and 64%, respectively [44,45]. A similar fnding has also been observed in another study conducted in Jamaica, with 96% of men correctly responding to questions about prostate cancer [46].…”
Section: Discussionsupporting
confidence: 86%
“…By contrast, in comparison with other studies from different countries, this rate was better than that which has been reported in South Africa (45.7%) among men attending a urologic outpatient clinic [ 47 ] and in Uganda (54.1%) [ 48 ]. Regarding knowledge of the PSA test, we found that 53.1% had heard of it before, compared to 72.7% and 41.8% [ 44 , 45 ]. This value is a little bit higher than a survey conducted in Uganda in 2013 reported 52.1% [ 48 ].…”
Section: Discussionmentioning
confidence: 93%
“…Result of several studies have shown the public awareness of prostate cancer and support this view. [19][20][21] This study gives us the idea about the knowledge of prostate cancer, screening practice and positive attitude towards prostate cancer screening among the patients visiting Urology OPD in Kathmandu. The findings of this study indicate a need for increased public sensitization campaigns on prostate cancer and screening tests as to create awareness about its prevention and early detection.…”
Section: Resultsmentioning
confidence: 99%